(untitled) (Journal of the College of Basic Education, 2025)
The study aimed to identify the effect of using added relative weights on some types of strength among first-year middle school students, as the importance of the research lies in using added relative weights in comparison to body weight and identifying their effect and the extent of development in some types of strength among first-year middle school students. Due to the diversity of training devices and because the researcher is a physical education teacher, he noticed that there is some weakness in some types of strength among students. Therefore, the researcher resorted to studying this problem and trying to identify the best means to address this weakness. The researcher had the idea of ​​using added relative weights to develop the level of some types of strength among students. The researcher assumed that there are statistically significant differences between the results of the pre- and post-tests of the two research groups (control and experimental) in the level of some types of strength, and that there are statistically significant differences in the results of the post-tests between the two research groups (control and experimental) in the level of some types of strength. The researcher used the experimental method, by designing equivalent groups, to suit the nature of the research problem. The research community was determined intentionally, which was represented by first-year middle school students in Al-Shu’ara Intermediate School for Boys, aged (13-15) years old, totaling (367) students. One of the classes was chosen randomly by lottery. The students were divided into two groups, a control and an experimental group, with (20) students for each group. The percentage of the research sample from the original community was (10.90). After conducting statistical treatments for the results of the pre- and post-tests for the two research groups, the researcher concluded that the use of added relative weights led to a greater improvement in the experimental group than the control group in some types of strength among first-year middle school students. Therefore, the researcher recommended the necessity of using added relative weights in lessons in order to develop some types of .